Patient Empowerment Among Children and Adolescents with Inflammatory Bowel Disease (IBD) and Parents of IBD Patients -Use of Counseling Services and Lack of Knowledge About Transition - Kaul, Kalina; Schumann, Stefan; Felder, Jakob; Däbritz, Jan; de Laffolie, Jan; Justus Liebig University Giessen (My University, 2025)
Background: Children and adolescents with pediatric inflammatory bowel diseases (PIBD) face significant challenges, including emotional stress, social isolation, and interrupted education due to symptoms. Effective counseling and education empower these young patients and their families to actively participate in healthcare. This paper investigates the IBD needs analysis (CEDNA), focusing on counseling and transition services. Methods: The Study Group distributed questionnaires to PIBD patients and the parents of children and adolescents with PIBD across Germany, with all responses provided anonymously. We conducted a subgroup analysis based on patient age and time since diagnosis, as well as aspects of regional distribution and city size. Parents’ responses were analyzed by corresponding age groups to facilitate comparison with the patients’ responses. Results: From October 2021 to April 2022, 1158 questionnaires (patients 38.9%, n = 450; parents 61.1%, n = 708) were completed. In the group of 16–17-year-old patients, only 14.1% (n = 239) feel well informed about transition programs (parents 6.7% of n = 360). Depending on the disease duration, 2.1% to 6.9% of the patients surveyed (n = 292) feel well informed about PIBD (parents 3.3% to 7.5%, n = 361). Nutritional counseling is the most requested support service (patients 49.2%, n = 382; parents: service used for their children 41.9%, n = 578; parents: service used for themselves 46.1%, n = 575). Conclusions: PIBD patients, especially aged 12–17, lack knowledge and preparation for transition to adult care. While general PIBD management awareness is fair, targeted educational efforts are necessary. Trustworthy information sources and early, tailored counseling services could enhance transition experiences and improve long-term disease management and patient outcomes.
Keywords: ddc:610